2012
DOI: 10.1039/c1cc15139h
|View full text |Cite
|
Sign up to set email alerts
|

Antibody recognition of fluorinated MUC1 glycopeptide antigens

Abstract: The syntheses of various fluorinated MUC1 glycopeptide antigens and their specific binding to serum antibodies from mice immunized with natural and fluorinated TF(6)-MUC1-TTox conjugate vaccines are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…1417 They have been conjugated to tetanus toxoid carrier protein and the conjugate vaccines elicited strong and specific immune responses in mice. 1819 These “foreign” fluorinated TACA-based vaccines not only provided enhanced immunogenicity and metabolic stability but also improved bioavailability. Despite the broad application of fluorine substitution in medicinal chemistry for generating several blockbuster drugs in the market (such as Lipitor ™ and Prozac ™ , etc.…”
Section: Introductionmentioning
confidence: 99%
“…1417 They have been conjugated to tetanus toxoid carrier protein and the conjugate vaccines elicited strong and specific immune responses in mice. 1819 These “foreign” fluorinated TACA-based vaccines not only provided enhanced immunogenicity and metabolic stability but also improved bioavailability. Despite the broad application of fluorine substitution in medicinal chemistry for generating several blockbuster drugs in the market (such as Lipitor ™ and Prozac ™ , etc.…”
Section: Introductionmentioning
confidence: 99%
“…[21] One reason for these failures is the sensitivity of TACAs to endogenous glycosidases, which reduces their in vivo bioavailability. [22][23][24] As a consequence, structural modifications to native TACAs, including the use of C-and S-glycosides, [25][26][27] deoxyfluoroglycosides, [28][29][30] truncated antigens, [31] or thioether-bridged mimetics, [32] have been proposed to provide structures more stable than those of the parent antigens without interfering with their B-cell immunogenicity. [33,34] In this study, we hypothesized that TACA-based vaccines displaying mimetics instead of native Tn antigens could be more resistant to enzymatic degradation.…”
mentioning
confidence: 99%
“…This example clearly suggests that increasing the polar hydrophobicity may help improve biological activity. Furthermore, the group of Hoffmann–Röder made a significant contribution in the preparation of various fluorinated MUC1 glycopeptide antigens, along with the preparation of the corresponding conjugate vaccines . Trifluorinated Thomsen–Friedenreich (TF) analogue 5 was used in immunization studies and binding experiments with antiserum obtained from immunization with a conjugate vaccine carrying the TF antigen glycan.…”
Section: Introductionmentioning
confidence: 99%
“…[11] This example clearly suggests that increasing the polar hydrophobicity mayh elp improve biological activity.F urthermore, the group of Hoffmann-Rçder made as ignificant contribution in the preparation of various fluorinated MUC1 glycopeptide antigens, [12] along with the preparation of the correspondingc onjugate vaccines. [13] Trifluorinated Thomsen-Friedenreich (TF) analogue 5 was used in immunization studies and binding experimentsw ith antiserum obtained from immunizationw ith ac onjugate vaccine carrying the TF antigen glycan.T he antisera derived from fluoroglycoconjugates showeds mall differences in binding to the fluorinated antigens. This work showed that fluorinated tumora ssociated carbohydrate antigensc ould be used for the design of vaccines with enhanced metabolic stability.…”
Section: Introductionmentioning
confidence: 99%